Analisis Audit Energi Terhadap Intensitas Konsumsi Energi Listrik Sistem Pencahayaan dan Sistem Penyimpanan Ikan di Cold Storage Kabupaten Malang - Ahmad Hermawan; Asfari Hariz Santoso; Sugeng Harianto (Elposys: Jurnal Sistem Kelistrikan, 2021)
Energy audit is one of the processes in managing energy use to bec ome more efficient. The purpose of this study was to determine the potential for energy savings that can be carried out optimally and accurately in Cold Storage, Malang Regency. Data retrieval using a Web-based Power Quality Meter PM5110 which is carried out for 24 hours on weekdays, then the total consumption of kWh in one day reached 119,538 kWh, while the total usage of kWh in one month is 3586.14 kWh for the month of June and for the total usage for the period of one year is 43631.37 kWh. Regarding the value of energy consumption kWh in a period of one year, it can be generated by dividing the total energy consumed by the building in one year by the total gross floor area of the building. Based on the results of the IKE calculation in the Cold Storage Building, Malang Regency from the results before the recommendation of 34.91 kWh/m2/year and for the result after the recommendation is 174,841 kWh/m2/year, which is included in the very efficient category according to the ASEAN USAID 1987 standard. For energy saving opportunities in the lighting system and cooling system, it can be done by using energy-efficient lamps and changing the operating pattern in the cooling room.